PENGARUH FAKTOR METEOROLOGIS DAN KONSENTRASI PARTIKULAT (PM10) TERHADAP KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) (Studi Kasus Kecamatan Banjarbaru Selatan, Kota Banjarbaru Tahun 2014-2015) - Wiji Cahyadi; Basir Achmad; Eko Suhartono; Fakhrur Razie (EnviroScienteae, 2016)
The purpose of this study was to analyze the influence of meteorological factors directly or indirectly through the concentration of particulate (PM10) on the incidence of Acute Respiratory Infections (ARI) in the District of South Banjarbaru, Banjarbaru. The method used in this research is cross-sectional study, where data meteorological factors, the concentration of particulate matter (PM10) and the incidence of ARI are collected simultaneously. Data meteorological factors and the concentration of particulate matter (PM10) derived from Banjarbaru Climatological Station, while data came from health ARI Banjarbaru and Sei Besar which is located in the district of South Banjarbaru. While the analysis used in this study were Path Analysis (path analysis) was an analysis of the relationship between the independent variables, intermediate variables, and the dependent variable was presented in the form of a diagram. The results showed the meteorological factors that had a direct impact on the incidence of ARI was the largest factor relative air humidity of by 18.7%, followed by a factor of 7.1% of air temperature, wind speed factor and its influence on the intensity of rainfall was below 1%. While the indirect influence of meteorological factors on the concentration of particulate matter (PM10) on the incidence of ARI in the District of South Banjarbaru effect was below 1%. It can be concluded that the direct effect of meteorological factors and the concentration of particulate matter (PM10) on the incidence of ARI in the District of South Banjarbaru significant factor was the relative air humidity and air temperature. While the indirect influence of meteorological factors against ARI through PM10, the effect was not significant.